Аctivating the problem of forming flexible skills in student-athletes - Obukhova O.V.; Ponomarev A.V.; Podkovyrkin M.N.; Tochilova I.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the demand for developing soft skills among student-athletes of the Ural Federal University (UrFU) as a model university in terms of organizing work with student-athletes. Methods and structure of the study. The experiment was conducted in November-December 2023 using an online questionnaire (Yandex form). 150 student-athletes took part in the survey: 55% boys and 45% girls. Results and conclusions. The educational organization of UrFU has a fairly developed sports base, which satisfies not only the needs of amateur athletes, but also professionals. This gives students a sense of care and interest in developing their sporting achievements. Student-athletes, receiving professional education, are focused on the quality of education and are ready to make additional efforts for self-development. Students are aware of the importance of soft skills for professional growth and self-development; most of them are focused on the development of communication, cognitive and organizational skills. Student-athletes assign priority soft skills to a specific sport.